Reliability and construct validity of the Ottawa valve collapse scale when assessing external nasal valve collapse - Hedyeh Ziai; James P. Bonaparte (Journal of Otolaryngology - Head and Neck Surgery)
Abstract Background Nasal valve collapse is a common cause of nasal obstruction in otolaryngology practice. Common examination methods, such as the Cottle Maneuver and modified Cottle Maneuver are available. However, these methods are dichotomous and do not provide ordinal severity information. The Ottawa Valve Collapse Scale (OVCS) is a grading system for assessing and easily grading external nasal valve collapse in patients with a septal deviation. The primary objective was to assess the test-retest reliability and construct validity of the OVCS grading scale. A secondary objective was to perform the same assessments on the Cottle Maneuver. Methods Patients with a septal deviation who were requesting surgical correction were prospectively enrolled in the study. All patients were assessed using both the Cottle Maneuver and the OVCS by one otolaryngologist at two visits separated by one month. The phi coefficient was calculated to assess the test-retest reliability of the instruments. Results of the Nasal Obstruction Symptom Evaluation (NOSE) Score was compared to determine construct validity. Results Ninety-two patients met our inclusion criteria. The phi coefficient was 0.62 for the OVCS and 0.32 for the Cottle Maneuver. The scores on the NOSE instrument were positively associated with the OVCS scores (p = 0.01) while there was no association with the Cottle Maneuver (p = 047). Conclusion This current preliminary analysis suggests that the novel Ottawa Valve Collapse Scale has good test-retest reliability and construct validity. This scale may help clinicians grade external nasal valve collapse in patients with a septal deviation. Future studies are required to determine if this scale assists surgeons in determining which patients need formal nasal valve surgery in addition to a standard septoplasty.